Język polityka, polityka w języku/Polityka na języku Rozważania na temat werbalnych form kontaktu z wyborcami polskich działaczy politycznych (analiza internetowych wydań środków społecznego przekazu u schyłku pierwszego dziesięciolecia XXI w.) - Wiśniewska, Paulina (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2009)
Odpowiednio dobrane i wypowiedziane słowa stanowią ważny przedmiot troski kreatorów wizerunku polityków, a przede wszystkim samych działaczy sceny politycznej. Teoretycznie, polityk jest obowiązany posługiwać się polszczyzną jasną, klarowną, spójną, logiczną, a nade wszystko - poprawną; słowo w ustach polityka powinno prowadzić do czynów, a nie zadowalać samospełnieniem. Polską codzienność stanowi jednak agresywny język debat parlamentarnych, czy mało wyszukane – wręcz obraźliwe określenia kierowane w stronę opozycji politycznej.

Appropriately selected and uttered words are a significant point of concern for the creators of a politician's image, primarily the image of actors on the political stage. Theoretically, a politician is obligated to use simple, clear, cohesive, logical – and first and foremost – correct language. A word uttered by a politician should stimulate activity and not be content with itself. Polish reality, however, is characterized by the aggressive language of parliamentary debates or unsophisticated, or plainly offensive, expressions directed at the political opposition.
A Politician's Language, Politics in the Language/Politics in Speech. Considerations on the Verbal Forms of Contact between Polish Political Activists and Their Voters (an analysis of Internet issues of public media in the end of the first decade of the 21st century)
Keywords: Język; Polityka